Factors influencing affinity of eSewa-Mobile Wallet: A case study in Kathmandu Valley - Nepal, Sweta (Nepalese Journal of Management, 2024)
This study examines the factors influencing user’s affinity of eSewa (mobile wallet) in Kathmandu Valley. User’s affinity towards eSewa is the dependent variable. The selected independent variables are transaction convenience, compatibility, ease of use, perceived security, perceived trust and rewards and offers. The primary source of data is used to assess the opinions of respondents regarding transaction convenience, compatibility, ease of use, perceived security, perceived trust and rewards and offers provided by mobile wallet in Kathmandu Valley. The study is based on primary data of 123 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of transaction convenience, compatibility, ease of use, perceived security, perceived trust and rewards and offers on user’s affinity towards eSewa mobile wallet.The study showed a positive impact of transaction convenience on user’s affinity. It indicates that providing transaction convenience to the users leads to increase in user’s affinity towards eSewa. The study showed a positive impact of compatibility on user’s affinity. This implies that compatible system leads to the increase in user’s affinity towards eSewa. The study also revealed a positive impact of ease of use on user’s affinity. It implies that user friendly system leads to increase in user’s affinity towards eSewa. Likewise, the study observed a positive impact of perceived security on user’s affinity. It indicates that secured system leads to increase in user’s affinity towards eSewa. Similarly, the study observed a positive impact of perceived trust on user’s affinity. It implies that higher level of trust towards the mobile wallet drives user’s affinity towards eSewa. Rewards and offers has a positive impact on user’s affinity. It shows that the frequent rewards and offers stimulates user’s affinity towards eSewa mobile wallet. The regression also shows that the beta coefficients are positive for transaction convenience, compatibility, ease of use, perceived security, perceived trust and rewards and offers are significant for all the independent variables at one percent level of significance.